Meta-information censorship and the creation of the Chinanet Bubble - Paltemaa Lauri; Vuori Juha A.; Mattlin Mikael; Katajisto Jouko (Routledge, 2022)
The question of who controls meta-information online has become a hot-button issue with profound political implications. The present article explores how state-led online censorship in the People’s Republic of China can create information bubbles, and how it is possible to analyze them. The article is based on a systematic comparison between 3,000 Google.com and Baidu.com image search results on a series of selected, potentially sensitive, keywords. This allows us to discern how censorship and information bubbles are connected, and how it is possible to detect and analyze them. To facilitate this, we offer a typology for conceptualizing the different dimensions of internet censorship. Our analysis points to the importance of censorship on metainformation and suggests that generally censored internet contents can also spill over to a liberal context through the Sinophone internet.